Global quality control perspective for the physical and technical aspects of screen-film mammography--image quality and radiation dose - Ng, Kwan Hoong; Jamal, N.; DeWerd, L. (Oxford University Press, 2006)
The systematic monitoring of image quality and radiation dose is an ultimate solution to ensuring the continuously high quality of mammography examination. At present several protocols exist around the world, and different test objects are used for quality control (QC) of the physical and technical aspects of screen-film mammography. This situation may lead to differences in radiation image quality and dose reported. This article reviews the global QC perspective for the physical and technical aspects of screen-film mammography with regard to image quality and radiation dose. It points out issues that must be resolved in terms of radiation dose and that also affect the comparison.